Comparative Study of the National Defense Curriculum in Universitas Pertahanan and Universitas Pembangunan Nasional “Veteran” Jawa Timur - Sutrisno; Anajeng Esri Edhi Mahanani; Teddy Prima Anggriawan; Alvian Dwiangga Wijaya (Nusantara Science and Technology Proceedings, 2021)
The university's identity which in this case is intended as "branding" becomes an urgent matter to be formulated as well as possible. The competition of each university in recruiting prospective students is not only in terms of quantity but also guarantees the quality of graduates. UPN “Veteran” Jawa Timur, which is known as the state defense campus, must formulate the values ??of state defense that will be implemented and become an identity that is not only a formality but can also truly reflect the quality of students who have a view of defending the country. The view of defending the state is the view and attitude that this country needs for every young generation of the nation. This research will try to formulate a model or reconstruct a model of implementing the values ??of defending the country in ideal teaching and learning activities, by comparing it to the Defense University which also applies the spirit of defending the country. This research is also expected to be a form of contribution from UPN "Veteran" East Java to the local community, nation, and state.